2017
DOI: 10.21037/jtd.2017.07.02
|View full text |Cite
|
Sign up to set email alerts
|

The detectability of the pretreatment EGFR T790M mutations in lung adenocarcinoma using CAST-PCR and digital PCR

Abstract: Background: A gatekeeper T790M mutation is thought to cause resistance to epidermal growth factor receptor tyrosine kinase inhibitor (EGFR-TKI) treatment. The detection of a 2nd mutation is important for planning the next therapy when patients acquire resistance to the first line EGFR-TKI. Conclusions: Our study shows that the pretreatment incidence of T790M mutation was less than that reported in previous studies. In order to clinically use pretreatment EGFR T790M mutation identification method, we should cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Using ddPCR, Watanabe and colleagues detected the EGFR T790M mutation in 79.9% of cases (298 of 373) in a concordant population and the same ddPCR approach (21). Two other ddPCR-based studies have reported an EGFR T790M mutation frequency of 40% and 100% for pretreated samples assessed (34,35); the large range of frequency might be explained by the limited size of the tested populations, with 20 and 13 cases, respectively. In this study, we observed a clear advantage of ddPCR compared with conventional techniques (HRM and direct sequencing), as the former was capable of detecting the EGFR T790M mutation when present at very low frequency, even as low as 0.0009% of total DNA.…”
Section: Discussionmentioning
confidence: 99%
“…Using ddPCR, Watanabe and colleagues detected the EGFR T790M mutation in 79.9% of cases (298 of 373) in a concordant population and the same ddPCR approach (21). Two other ddPCR-based studies have reported an EGFR T790M mutation frequency of 40% and 100% for pretreated samples assessed (34,35); the large range of frequency might be explained by the limited size of the tested populations, with 20 and 13 cases, respectively. In this study, we observed a clear advantage of ddPCR compared with conventional techniques (HRM and direct sequencing), as the former was capable of detecting the EGFR T790M mutation when present at very low frequency, even as low as 0.0009% of total DNA.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, when tumor samples were classified into two groups based on the abundance of T790M-MAF, multivariate analysis demonstrated that high-preT790M was the independent factor related to a poor prognosis (RFS), irrespective of patient background, including pathological stage, age, and sex. A previous retrospective study by Tatematsu et al, which analyzed the incidence of minor-frequency preT790M using competitive allele-specific PCR in 153 surgically resected EGFR -mutated lung adenocarcinoma tissues, the incidence of preT790M was 29.4%, and T790M-MAF ranged from 0.13 to 2.65% (median MAF 0.20%) [ 36 ]. However, in their study, no significant impact of preT790M on RFS was shown.…”
Section: Discussionmentioning
confidence: 99%
“…The reason we did not nd co-existing de novo T790M and 19 Del in our study perhaps because of the small sample size and rare de novo T790M cases. However, it was reported that acquired T790M mutation always coexist with 19Del [20][21][22]. Tian's study [22] reported that the ratio of allele frequency (Relative allele frequency, RAF) of the T790M mutation to the EGFR sensitizing mutation was different between the de novo and acquired T790M mutations (86.1% vs. 22.3%, P< 0.0001).…”
Section: Discussionmentioning
confidence: 99%